Managing Sales Pipelines In Technology-Driven Markets: Integrating New Business Development With Publisher-Centric Monetization Models - Rubinstein, Itay (Journal of International Crisis and Risk Communication Research, 2024)
In technology-driven markets characterized by platform-based distribution and publisher-dependent revenue ecosystems, traditional sales pipeline management approaches often fail to capture the monetization potential of supply-side partnerships. This study examines the integration of new business development (NBD) processes with publisher-centric monetization models to enhance pipeline conversion efficiency and long-term revenue sustainability. Using a quantitative analytical framework, the research evaluates the influence of monetization performance indicators including platform monetization efficiency (PME), publisher onboarding rate (POR), inventory utilization ratio (IUR), fill rate (FR), and revenue per publisher (RPP) on key pipeline outcomes such as pipeline conversion ratio (PCR), average deal closure time (ADCT), revenue realization rate (RRR), and customer lifetime value (CLV). Multivariate regression and structural modelling results reveal that PME significantly improves conversion efficiency and revenue realization while reducing deal closure timelines. Furthermore, clustering analysis highlights structural heterogeneity in pipeline–monetization integration across firms, suggesting that early-stage alignment between opportunity qualification and monetization readiness enhances revenue scalability. The findings underscore the importance of embedding publisher monetization intelligence within sales pipeline governance frameworks to support resilient, value-driven growth strategies in digitally mediated market environments.